Toward culturally responsive psychology higher education courses: psychologists’ perspectives on preparedness to work with Aboriginal and Torres Strait Islander clients - Emily Darnett; Andrew Peters; Monica Thielking (Australian Journal of Psychology)
Background Psychology course regulatory standards for Australian universities have evolved in that universities are required to include cultural responsiveness in psychology curriculum and demonstrate graduate competencies for working with Aboriginal and Torres Strait Islander clients.Aim This study aimed to explore psychologists’ perspectives about the higher education (HE) psychology curriculum in relation to their preparedness to practice with Aboriginal and Torres Strait Islander clients and share their suggestions for improving cultural responsiveness and preparedness.Method Psychologists (N=108, Female 83.2%, Male 16.8%, Aboriginal 13.9%, non-Indigenous 86.1%, age range 22–83) responded to an electronic mixed-method survey.Findings The majority of participants (91.43%, including all Aboriginal psychologists) reported that their psychology HE training did not adequately prepare them to work with Aboriginal and Torres Strait Islander clients. Moreover, 87.5% (Group 3 n=16) reported apprehensions about working with Aboriginal and Torres Strait Islander clients for the first time. Limited understanding of culture, concerns for their competence, or worry about perpetuating harm underpinned psychologists’ apprehensions. Most participants (90.5%, n=85) indicated they plan to increase their knowledge in this area. Non-Indigenous participants suggested that the psychology curriculum should incorporate increased exposure to lived experiences (28%), Indigenous-specific information (e.g. the impact of intergenerational trauma; 24%), more practical exercises (20%), and guidelines for adapting existing clinical interventions (28%). The study also revealed indicators of racially motivated biases in some participants’ responses.Conclusion All Aboriginal and the majority of non-Indigenous participants reported that HE psychology training did not adequately prepare them to work with Aboriginal and Torres Strait Islander clients.